2016
DOI: 10.1136/bmjopen-2016-013806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of lifestyle interventions for the prevention of diabetes: an overview of systematic reviews

Abstract: ObjectivesTo review the clinical outcomes of combined diet and physical activity interventions for populations at high risk of type 2 diabetes.DesignOverview of systematic reviews (search dates April–December 2015).SettingAny level of care; no geographical restriction.ParticipantsAdults at high risk of diabetes (as per measures of glycaemia, risk assessment or presence of risk factors).InterventionsCombined diet and physical activity interventions including ≥2 interactions with a healthcare professional, and ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…An interesting finding from our study was that TPA was particularly important for older women with i-IFG or i-IGT in terms of normalizing their blood glucose levels. A number of studies examining the effect of different lifestyle interventions on diabetes prevention in individuals with prediabetes have studied whether the effect of the various interventions differ across sex and age in subgroup analyses ( 33 ). Most intervention studies found no sex differences in the effect of lifestyle interventions on diabetes prevention or changes in glycemic parameters in individuals with prediabetes ( 33 , 34 ), potentially because they were underpowered to look at those interactions or because higher order interactions with other parameters ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding from our study was that TPA was particularly important for older women with i-IFG or i-IGT in terms of normalizing their blood glucose levels. A number of studies examining the effect of different lifestyle interventions on diabetes prevention in individuals with prediabetes have studied whether the effect of the various interventions differ across sex and age in subgroup analyses ( 33 ). Most intervention studies found no sex differences in the effect of lifestyle interventions on diabetes prevention or changes in glycemic parameters in individuals with prediabetes ( 33 , 34 ), potentially because they were underpowered to look at those interactions or because higher order interactions with other parameters ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a typical lifestyle-related disease 1. The course of T2DM and potential complications are influenced by smoking behaviour,2 3 BMI4 and physical exercise 5.…”
Section: Introductionmentioning
confidence: 99%
“…Preventing or delaying diabetes incidence has become a real challenge in all public health systems [1]. The efficacy of clinical trials on lifestyle interventions for diabetes prevention has been wellestablished [2,3], and efforts to translate these interventions to primary care settings have shown promising results [4][5][6]. Long-term projections have also shown that diabetes can be postponed by an average of 5 years in people who already have pre-diabetes [7].…”
Section: Methodsmentioning
confidence: 99%
“…An additional reason might be that translation channels do not work properly. In all, this could result in an increase of the consequences of diabetes, a waste of public resources and a loss of potential health benefits [5,8].…”
Section: Methodsmentioning
confidence: 99%